Prevalence, risk factors, and viral load quantification of HBV infection among hospital patients: A cross-sectional investigation in Mogadishu, Somalia - Bashiru Garba; Amino Adan Mohamud; Fartuun Hassan Mohamed; Ayan Aden Moussa; Yusuf Yakubu; Najib Isse Dirie; Aya Muktar Abdulatif; Jamal Hassan Mohamoud; Abdirasak Sharif Ali; Abdurrahman Hassan Jibril (PLoS ONE, 2026)
Background Hepatitis B virus (HBV) remains a major public health challenge in sub-Saharan Africa. Somalia, with its fragile healthcare system and high-risk population, lacks up to date data on HBV epidemiology. This study assessed HBV prevalence, associated risk factors, and viral load among hospital patients in Mogadishu, Somalia. Methods A cross-sectional survey was conducted in four major hospitals in Mogadishu. Socio-demographic and clinical risk data were collected using structured questionnaires. Blood samples from 270 participants were screened for HBsAg using a rapid test, with positives confirmed and quantified for HBV DNA by real-time PCR. Bivariate and multivariate analyses identified independent risk factors. Results HBsAg prevalence was 11.5% (n = 31), but only 2.2% of all participants (6/270; 19.4% of HBsAg-positives) had detectable HBV DNA. The strongest independent predictors were family history of HBV (AOR: 5.08, 95% CI 1.90–13.60) and history of tooth extraction (AOR: 3.18, 95% CI 1.24–8.12). Socio-economic factors, facility variations, and low vaccination were also observed. Classical behavioral risk factors were infrequent and not significant. Among PCR positive cases, only one presented with a high viral load (>20,000 IU/mL). Conclusion HBV poses a substantial, ongoing threat to the Somali population, especially in hospital-based settings. Household transmission and unsafe medical procedures are the most significant risk factors. Improving infection control, expanding vaccination, and prioritizing molecular diagnostics will be critical to effective HBV control in Somalia.